Analisis Kenaikan Muka Air Laut di Belawan - Arrisha Anggraini; Ahmad Perwira Mulia; Gina Cynthia R Hasibuan; M. Faisal (Jurnal Syntax Admiration, 2023)
Climate change can cause an increase in sea temperatures which will have an impact on sea level rise due to the expansion of sea water volume and melting ice at the poles. Rising sea levels pose a threat to areas in coastal and coastal areas, one of which is Medan Belawan District. One of the impacts is tidal flooding. Tidal floods caused by high tides are then exacerbated by the phenomenon of rising sea levels so that it becomes a factor in increasing tidal flood inundation. The purpose of this study is to analyze sea level rise in Medan Belawan District by processing tidal data for 2012-2022 and sea level anomalies for 1993-2022 in the rate of sea level rise. The method used to calculate the tidal component uses the Admiralty method, sea level rise uses the linear regression method. The results of this study show that the value of sea level rise based on tidal data is 0.22 mm/year and 4.5 mm/year based on altimetry satellite data.